2022
DOI: 10.1126/science.abj1861
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic axon origin enables information gating by perisomatic inhibition in pyramidal neurons

Abstract: Information processing in neuronal networks involves the recruitment of selected neurons into coordinated spatiotemporal activity patterns. This sparse activation results from widespread synaptic inhibition in conjunction with neuron-specific synaptic excitation. We report the selective recruitment of hippocampal pyramidal cells into patterned network activity. During ripple oscillations in awake mice, spiking is much more likely in cells in which the axon originates from a basal dendrite rather than from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Such analyses could also assess the role of neurons with basal dendrites that act as axons during theta vs . non-theta ripples (Hodapp et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analyses could also assess the role of neurons with basal dendrites that act as axons during theta vs . non-theta ripples (Hodapp et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While these are technically challenging experiments, the availability of multielectrode recording probes along with high-resolution voltage imaging and other recording techniques in awake behaving animals make such analyses feasible (Giocomo, 2015;Abdelfattah et al, 2019;Steinmetz et al, 2021;Valero et al, 2022;Zong et al, 2022). Such analyses could also assess the role of neurons with basal dendrites that act as axons during theta vs. non-theta ripples (Hodapp et al, 2022). 0.0012, imm.…”
Section: Experimental Designs and Analysis Pipelines Should Explicitl...mentioning
confidence: 99%
“…While most studies of neuronal signal integration focus on dendrites [ 8 ], more recent work points towards the importance of the axon’s location and properties [ 6 ]. Hodapp and coworkers 4 have now reported a new computational mechanism in cortical networks which is based on the location of the axon. Previous work by the same group had shown that in up to 50% of mouse hippocampal pyramidal cells, the axon emanates from a basal dendrite, rather than from the soma [ 10 ].…”
mentioning
confidence: 99%
“…During strong inhibition, the axon-carrying dendrite is the most likely source of excitation for action potential generation. Scale bar, 20 μm (adapted from [ 4 ] …”
mentioning
confidence: 99%
See 1 more Smart Citation